Numerical Study of Cooling Air Flow Distribution in Car Cabin - Jamaldi, Agus (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2021)
This numerical study aims to investigate the performance of car air-conditioning (AC) cooling of cabin car. The research was done in the two-step. The first step is to collect data by experiment study. Numerical study of performance car air-conditioning is the second step. Detached Eddy Simulation k-epsilon (DES k-Îµ) turbulence model was utilized in the study. A cabin car design was used as a specimen study. Two key parameters, i.e. temperature distribution, and air cooling speed, were used to assess the AC cooling performance compared with experimental data. Two types of mesh (mesh A and B) with different smooth was utilized. The results showed that mesh B gave good agreement with experimental data with a discrepancy of 0.14%, and 0.27% with mesh A. Air cooling distribution at three measured positions are 0.47; 0.08; and 0.04 m/s, respectively.